Imaging in staging, treatment planning, and monitoring of hepatocellular carcinoma for local and locoregional therapies: consensus recommendations from EORTC and ESGAR - Öcal, Osman; Zech, Christoph Johannes; Bali, Maria Antonietta; Pasquier, David; Mottaghy, Felix; Einspieler, Ingo; Kartalis, Nikolaos; Bargellini, Irene; Iezzi, Roberto; Denecke, Timm; Kunz, Wolfgang Gerhard; Gebauer, Bernhard; et al. (European radiology, 2025)
Background: Periinterventional imaging of patients with hepatocellular carcinoma (HCC) during local and locoregional therapies plays a crucial role in clinical outcome by guiding treatment allocation, planning, and application. However, there is a considerable variety in clinical routine in terms of timing, modality, and imaging protocols. This study aimed to guide the standardization of the imaging procedures for patients with HCC by conducting a Delphi consensus-finding survey. Methods: A multidisciplinary, multinational survey was conducted to standardize the imaging of patients with HCC using the Delphi method. Results: Under the guidance of the European Organisation for Research and Treatment of Cancer (EORTC) Imaging and Gastrointestinal Tract Cancer Groups and the European Society of Gastrointestinal and Abdominal Radiology (ESGAR), the recommendations for imaging before, during, and after thermal ablation, transarterial chemoembolization, radioembolization, and stereotactic body radiation therapy were established. Conclusion: This consensus protocol provides a foundational guide for imaging in the daily clinical management of HCC patients, as well as for prospective studies assessing local and locoregional therapies.